2023
DOI: 10.1186/s12935-023-03054-x
|View full text |Cite
|
Sign up to set email alerts
|

The pyrazole derivative of usnic acid inhibits the proliferation of pancreatic cancer cells in vitro and in vivo

Mariola Gimła,
Agnieszka Pyrczak-Felczykowska,
Marcelina Malinowska
et al.

Abstract: Background Pancreatic cancer is one of the leading causes of cancer death in Western societies. Its late diagnosis and resistance to chemotherapies result in a high mortality rate; thus, the development of more effective therapies for the treatment of pancreatic cancer is strongly warranted. Usnic acid (UA) is a secondary metabolite of lichens that shows modest antiproliferative activity toward cancer cells. Recently, we reported the synthesis of a UA pyrazole derivative, named 5, which was mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Usnic acid, a furan metabolite derived from the botanical drug Usnea diffracta Vain, has anti-inflammatory and anti-tumor effects ( Xie LS et al, 2023 ). Gimła M et al (2023) demonstrated that usnic acid upregulated the expression of BIP, IRE1α and GADD153 in human PDA cells MIA PaCa-2 and PANC-1, blocking the cell cycle at G0/G1, inhibiting tumor growth and inducing apoptosis.…”
Section: Chinese Botanical Drug Extracts Against Digestive System Tum...mentioning
confidence: 99%
“…Usnic acid, a furan metabolite derived from the botanical drug Usnea diffracta Vain, has anti-inflammatory and anti-tumor effects ( Xie LS et al, 2023 ). Gimła M et al (2023) demonstrated that usnic acid upregulated the expression of BIP, IRE1α and GADD153 in human PDA cells MIA PaCa-2 and PANC-1, blocking the cell cycle at G0/G1, inhibiting tumor growth and inducing apoptosis.…”
Section: Chinese Botanical Drug Extracts Against Digestive System Tum...mentioning
confidence: 99%
“…Although the therapeutic intervention for PC has improved, tumor-related deaths caused by metastasis and recurrence remain a major challenge [ 4 ]. Once PC is diagnosed, the vast majority of cases show distant metastasis [ 5 ]. In addition, PC is less sensitive to radiotherapy, chemotherapy, and immunotherapy because of its intra-tumoral heterogeneity in cell metabolism, which is important for tumor growth and metastasis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%